Platinum instability in PEM fuel cells MEA’s subjected to chloride contamination - Rangel, C. M. (2012)
In this work a low power fuel cell, intended for passive management of water, was operated integrating a range of relative humidity (RH) from ~30 to 80% and temperatures from 5 to 55 ºC. The stack was fed with pure hydrogen. An open air cathode was designed for easy water removal and stack cooling. The stack uses own design flow field drawn on graphite plates from Schunk and a commercial MEA with carbon supported catalyst containing 0.3 mgcm-2 Pt. Polarization curves were registered for a full stack characterization using a purpose-built test station and a climatic chamber with temperature and RH control. Results indicated that 60% RH is associated to maximum fuel cell performance over the studied temperature range. While water management is done in a passive fashion, heat management is done on the basis of the injection of air at the cathode with the fuel cell showing good performances at relatively low currents where back diffusion towards the anode is favored. The loss of performance with temperature increase was related to an increase in the membrane resistance which may correspond to loss of water on the anode side. Performances at temperatures lower that room temperature showed only slight decrease in power. An examination of the fuel cell components after 100 h of operation revealed that chloride contamination has produced cathode failure associated to catalyst migration anomalies favored by operation conditions that allowed platinum particles to break free from their carbon backing and migrate toward the polymer electrolyte. Migration resulted in precipitation with larger mean particle size distribution within the solid electrolyte when compared to the original catalyst layer, rendering a very significant loss of thickness in the cathode material. Coarsening of platinum particles occurs at nano and micro-scale. The mechanism for the lost of catalyst by dissolution and growth is discussed on the basis of a joint electrochemical and SEM/TEM study.